PERLINDUNGAN HUKUM BAGI PEMEGANG HAK ATAS TANAH DALAM HAL TERDAPAT SERTIPIKAT GANDA - Wandha Noviaditama, Hj. Endang Sri Santi, Triyono (Diponegoro Law Journal, 2012)
According to the National Land Agency, the number of parcles of land in Indonesia is now no less than 80 million plane. When considering the main points of BAL clear objectives that should land the plane, have to be given legal certainty for the owners of the parcels of land in question. However, the reality is not so, for the achievement od land registration is done up to now has not been as expected. Thus there are many plots that do not have legal certainty. This shows how much the burden borne by the BAL to alleviate the legal uncertainty regarding the rights of the land to the owners of land in Indonesia. The purpose of this study was to determine the factors causing multiple certificates to Semarang city and for the consideration of the judges already know or do not conform with the provisions of the law in deciding disputes multiple certificates. The research was conducted using the normative jurdicial approach to discover and get to know whether and how  the positive law of the particular problem. So the research approach used in this research is an approach that is normative juridical (Legal Research). The method of data collection was done by using the documentation, which is solely derived from the laws and decisions of the courts in resolving land disputes. Factors contributing to the dual certificate is due to incomplete registration maps, human factors, expansion area, improper administration in villages and spatial changes by the city goverment. Of all the factors mentioned above and the inaccuracy caused by negligence land office Semarang role in examining and researching the physical data and juridical data and assessment of the truth of the  evidence of land ownership by checking warkah land office is in the city of Semarang. Consideration of the judges on the incidence of multiple certificates can be reached by 2 ways, by resolving disputes through the nasional land agency and by resolving through the courts.